2012
DOI: 10.1016/j.biopsych.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Brain-Behavior Relationships in Children with Attention-Deficit/Hyperactivity Disorder

Abstract: Background Emerging neuroscientific and genetic findings emphasize the dimensional rather than the categorical aspects of psychiatric disorders. However, the integration of dimensional approaches within the current categorical diagnostic framework remains unclear. Here, we used resting state fMRI (R-fMRI) to examine whether dimensional measures of psychiatric symptomatology capture brain-behavior relationships unaccounted for by categorical diagnoses. Additionally, we examined whether dimensional brain-behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 58 publications
9
80
0
Order By: Relevance
“…Neuroimaging studies [126][127][128] have shown that individuals with ADHD have reduced functional independence between task-positive networks and the task-negative DMN compared with individuals without ADHD; these networks have an anti-correlated relationship during successful spatial attention 129 and cognitive control 130 …”
Section: Fugl-meyer Scoresmentioning
confidence: 99%
“…Neuroimaging studies [126][127][128] have shown that individuals with ADHD have reduced functional independence between task-positive networks and the task-negative DMN compared with individuals without ADHD; these networks have an anti-correlated relationship during successful spatial attention 129 and cognitive control 130 …”
Section: Fugl-meyer Scoresmentioning
confidence: 99%
“…However, the specific neuropsychological dysfunction underlying such atypical brain network profiles remains poorly understood (11). Patients with ADHD often exhibit deficiencies in cognitive function, particularly in executive functions such as strategic planning, set switching, cognitive flexibility, and interference inhibition (12), which can be defined by neuropsychological tests such as the Wisconsin Card Sorting Test (WCST) (13) and the Stroop ColorWord Test (14).…”
Section: Participantsmentioning
confidence: 99%
“…As an exploratory analysis, a hybrid model comprising both categorical and dimensional effects was also tested. The hybrid model, as for example, used earlier in functional MRI (Chabernaud et al, 2012;Elton et al, 2014), includes both categorical and dimensional predictors, and sometimes also their interaction regressor, in the same regression model, to better evaluate the existence of potential complementary, coexisting categorical or dimensional effects. Although FA is sensitive to alterations in white matter microstructure, there is no one-to-one relationship between FA and a particular physical or pathological property.…”
Section: Introductionmentioning
confidence: 99%